Hypo-Osmotic Loading Induces Expression of IL-6 in Nucleus Pulposus Cells of the Intervertebral Disc Independent of TRPV4 and TRPM7 - Sadowska, Aleksandra; Altinay, Birsen; Hitzl, Wolfgang; Ferguson, Stephen J.; Wuertz-Kozak, Karin (Frontiers in Pharmacology, 2020)
Painful intervertebral disc (IVD) degeneration is an age-related process characterized by reduced tissue osmolarity, increased catabolism of the extracellular matrix and elevated levels of pro-inflammatory molecules. With the aging population and constantly rising treatment costs, it is of utmost importance to identify potential therapeutic targets and new pharmacological treatment strategies for low back pain. Transient receptor potential (TRP) channels are a family of Ca2+ permeable cell membrane receptors, which can be activated by multitude of stimuli and have recently emerged as contributors to joint disease, but were wider not investigated in the IVD. Based on the gene array screening, TRPC1, TRPM7 and TRPV4 were overall the most highly expressed TRP channels in bovine IVD cells. We demonstrated that TRPV4 gene expression was down-regulated in hypo-osmotic condition, whereas its Ca2+ flux increased. No significant differences in Ca2+ flux and gene expression was observed for TRPM7 between hypo- and iso-osmotic groups. Upon hypo-osmotic stimulation, we overall identified via RNA sequencing over 3000 up- or down-regulated targets, from which we selected aggrecan, ADAMTS9 and IL-6 and investigated whether their altered gene expression is mediated through either the TRPV4 or TRPM7 channel, using specific activators and inhibitors (GSK1016790A/ GSK2193874 for TRPV4 and Naltriben/ NS8593 for TRPM7). GSK1016790A induced the expression of IL-6 under iso-osmotic condition, alike to hypo-osmotic stimulation alone, indicating that this effect might be TRPV4-mediated. However, using the TRPV4 blocker GSK2193874 failed to prevent the increase of IL-6 under hypo-osmotic condition. A treatment with TRPM7-activator did not cause significant changes in the gene expression of tested targets. In conclusion, while TRPV4 and TRPM7 are likely involved in osmosensing in the IVD, neither of them mediates hypo-osmotically-induced gene expression changes of aggrecan, ADAMTS9 and IL-6.